HUBUNGAN TINGKAT KECEMASAN, STRES DAN DEPRESI TERHADAP KUALITAS TIDUR MAHASISWA TINGKAT AKHIR SAAT MENYUSUN SKRIPSI DI FAKULTAS ILMU KESEHATAN UPN VETERAN JAKARTA TAHUN 2022 - Putri Suryani Arifah (2022)
Thesis is an academic demand for final year students whose completion there are obstacles and obstacles, this has an impact on increasing student tension and difficulty in starting to sleep. These difficulties can make it difficult for students to get the quality of sleep they want. Some of the causes of sleep disturbances in students when writing a thesis are feelings of anxiety, stress and depression. The purpose of this study was to determine the relationship between levels of anxiety, stress and depression on the quality of sleep of final year students when compiling a thesis at the Faculty of Health Sciences UPN Veterans Jakarta in 2022. This study used a cross-sectional study design with purposive sampling technique with 181 respondents. student. Collecting research data using online questionnaires using google form. The research instrument used was the DASS and PSQI questionnaires. This study used univariate and bivariate analysis with Chi-Square test. The results showed that there was a relationship between anxiety levels, stress levels and depression levels with the sleep quality of final year students when compiling their thesis (p=0.000) and OR=61.3 (95% CI: 20.0-188). .5), (p=0.000) and OR=12.2 (95% CI: 5.1-29.3) and (p=0.000) and OR=8.4 (95% CI: 3.2 -22.0). Based on this, students are expected to be able to manage stress in order to reduce levels of anxiety, stress and depression so as to improve the quality of student sleep.